2021
DOI: 10.3389/fmicb.2021.811939
|View full text |Cite
|
Sign up to set email alerts
|

Cold Shock Proteins Promote Nisin Tolerance in Listeria monocytogenes Through Modulation of Cell Envelope Modification Responses

Abstract: Listeria monocytogenes continues to be a food safety challenge owing to its stress tolerance and virulence traits. Several listeriosis outbreaks have been linked to the consumption of contaminated ready-to-eat food products. Numerous interventions, including nisin application, are presently employed to mitigate against L. monocytogenes risk in food products. In response, L. monocytogenes deploys several defense mechanisms, reducing nisin efficacy, that are not yet fully understood. Cold shock proteins (Csps) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…On the other hand, csp mutants were more tolerant than the WT on some substances, e.g., EGDe_∆cspABD was more tolerant than its WT on five substances. We also previously found that cspD expressed alone in an EGDe ∆cspAB mutant increased tolerance to antimicrobials such as nisin and daptomycin (Muchaamba et al, 2021b). The mechanisms underlying these phenotypes are unknown, but we can only currently speculate that Csp loss might cause an alteration in expression of genes that increase resistance.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…On the other hand, csp mutants were more tolerant than the WT on some substances, e.g., EGDe_∆cspABD was more tolerant than its WT on five substances. We also previously found that cspD expressed alone in an EGDe ∆cspAB mutant increased tolerance to antimicrobials such as nisin and daptomycin (Muchaamba et al, 2021b). The mechanisms underlying these phenotypes are unknown, but we can only currently speculate that Csp loss might cause an alteration in expression of genes that increase resistance.…”
Section: Discussionmentioning
confidence: 93%
“…At the mechanistic level, csp mutants were more sensitive to the cell wall and membrane-targeting substances such as cloxacillin and BC, suggesting a role for Csps in the proper function of these cellular systems. Recently, we demonstrated that, among other functions, Csps also affect the expression of Penicillin-binding protein genes and cell wall modification systems contributing to such stress responses ( Muchaamba et al, 2021b ). An explanation is that csp mutants could have altered cell wall structures that increase permeability to some chemicals and antibiotics thus increasing sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations